A simple all-PEDOT:PSS electrochemical transistor for ascorbic acid sensing1. Issue 33 (7th September 2015) - Gualandi, I.; Marzocchi, M.; Scavetta, E.; Calienni, M.; Bonfiglio, A.; Fraboni, B.
<x xml:space="preserve">Abstract</x> An all-PEDOT:PSS electrochemical transistor was used to detect ascorbic acid, which is an excellent platform for developing chemical sensors.